Effect of two-dimensional parity symmetry breaking in Aharonov-Bohm interference phenomena. Issue 174 (1st September 2016) - Xie, Yuantao; Heremans, J. J.; Santos, M. B.
ABSTRACT: The quantum-mechanical dephasing effect of a two-dimensional parity symmetry breaking is demonstrated in a solid-state quantum-coherent mesoscopic ring interferometer. The interferometer, fabricated on an InGaAs/InAlAs heterostructure, shows Aharonov-Bohm oscillations under magnetic fields at low temperatures. Under asymmetric bias voltage on side-gates, a weakening of the Aharonov-Bohm oscillations is observed. The weakening corresponds to an effective dephasing under two-dimensional parity symmetry breaking by the applied electric field, and is interpreted as a counterpart to the weakening observed under time-reversal symmetry breaking by a magnetic field.